Enrichment of Food With Tannin Extracts Promotes Healthy Changes in the Human Gut Microbiota - Molino, Silvia; Lerma-Aguilera, Alberto; Jiménez-Hernández, Nuria; Gosalbes, María José; Rufián-Henares, José Ángel; Francino, M. Pilar (Frontiers in Microbiology, 2021)
Food and food bioactive components are major drivers of modulation of the human gut microbiota. Tannin extracts consist of a mix of bioactive compounds, which are already exploited in food industry for their chemical and sensorial properties. The aim of our study was to explore the viability of associations between tannin wood extracts of different origin and food as gut microbiota modulators. 16S rRNA amplicon next-generation sequencing (NGS) was used to test the effects on the gut microbiota of tannin extracts from quebracho, chestnut and tara associated with commercial food products with different composition in macronutrients. The different tannin-enriched and non-enriched foods were submitted to in vitro digestion and fermentation by the gut microbiota of healthy subjects. The profile of the Short Chain Fatty Acids (SCFAs) produced by the microbiota was also investigated. The presence of tannin extracts in food promoted an increase of the relative abundances of the genus Akkermansia, recognized as a marker of a healthy gut, and of various members of the Lachnospiraceae and Ruminococcaceae families, involved in SCFA production. The enrichment of foods with tannin extracts had a booster effect on the production of SCFAs, without altering the profile given by the foods alone. These preliminary results suggest a positive modulation of the gut microbiota with potential benefits for human health through the enrichment of foods with tannin extracts.